Law Enforcement Process Analysis By Agencies Of Provos Indonesian National Police (Inp) On Discipline Violation In The Form Of Crime By Police Members (Case Study In National Police Headquarter) - Iwan Setiyadi; Sri Kusriyah Kusriyah (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Law enforcement is one attempt to create order, security and peace in the community, whether it is a preventive and repressive effort. Order and security in society will be realized and maintained properly if all the components of society in a country can understand and comply with all the norms contained in the social life. Police as one of the law enforcement agencies in Indonesia is the spearhead for the achievement of the rule of law in Indonesia. With separated INP from the Indonesian Army (TNI) then sued professionalism of members of the police in the execution of their duties. The aims of this research are, to know Provos INP in the law enforcement of discipline to member of Indonesian National Police (INP) who did violation on Disciplinary Code in Government Regulation No. 2 of 2003 on Disciplinary Code to all member of police as the explanation from Article 27 paragraph (2) Act No. 2 of 2002 on Indonesian National Police. After declared PP No. 2 of 2003, Provos INP has given authority as auditor to all members of Indonesian National Police who did violation even though the violation is not criminal sanction and give the document to Authorities Agency (Ankum). And to know the factors which impacted the law violation by Indonesian National Police in disciplinary code which not be burden by Provos INP to do Disciplinary Law Enforcement. Keywords: Discipline Violation; Provost INP; Crime.